Water-insoluble aerogels made from cellulose nanocrystals and poly(vinyl alcohol). Issue 4 (1st December 2014) - Foster, E. Johan; Mueller, Silvana; Weder, Christoph
Abstract : Cellulose nanocrystal (CNC) aerogels are attractive low-density materials, although the brittleness and/or water dispersibility can limit the usefulness of these materials. The authors report here the preparation of water-insoluble aerogels made by lyophilization of aqueous dispersions of low-aspect ratio CNCs extracted from cotton. Poly(vinyl alcohol) (PVOH) was added as a polymeric binder, and the PVOH- and the CNC-concentration ([PVOH] and [CNC]) as well as the freeze-drying conditions were systematically varied. The effect of these parameters on the morphology, mechanical properties and the specific surface area of the resulting CNC/PVOH aerogels was investigated. By increasing the PVOH-concentration, the stiffness of the aerogels increases by a factor of two, and varying the [CNC] as well as the freezing method leads to different pore morphologies. An environmentally friendly, isothermal annealing process was used to induce crosslinking without the need for auxiliary chemicals and was shown to decrease the water dispersibility and increase the stiffness by c . 50%. A more pronounced stiffness increase was achieved by chemically crosslinking the nanocomposite aerogels with sodium tetraborate (Na2 B4 O7 ), but in this case the water dispersibility was increased. This article contains supporting information that will be made available online once the issue is published.